Conductive magnetorheological elastomer: fatigue dependent impedance-mechanic coupling properties. (18th November 2016) - Wang, Yu; Xuan, Shouhu; Ge, Lin; Wen, Qianqian; Gong, Xinglong
Abstract: This work investigated the relationship between the impedance properties and dynamic mechanical properties of magnetorheological elastomers (MREs) under fatigue loading. The storage modulus and the impedance properties of MREs were highly influenced by the pressure and magnetic field. Under the same experimental condition, the two characteristics exhibited similar fatigue dependent change trends. When pressure was smaller than 10 N, the capacitance of MRE could be divided into four sections with the increase of the cyclic numbers. The relative equivalent circuit model was established to fit the experimental results of the impedance spectra. Each parameter of circuit element reflected the change of fatigue loading, relative microstructure of MRE, MRE-electrode interface layer, respectively. Based on the above analysis, the real-time and nondestructive impedance method was demonstrated to be high potential on detecting the fatigue of the MRE device.